2003
DOI: 10.1002/ajpa.10304
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different kinds of cranial deformation on the incidence of wormian bones

Abstract: Researchers have debated whether the presence and frequency of wormian bones (sutural bones, supernumerary bones, and ossicles) are attributable to genetic factors, environmental factors, or both. This research examines the effects of many different kinds of cranial deformation on the incidence of wormian bones. A sample of 127 deformed and undeformed crania from New World archaeological sites was examined. An undeformed cranial sample (n=35) was compared to the following cranially deformed groups: 1) occipita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 20 publications
0
83
0
4
Order By: Relevance
“…It has been suggested that this may occur due to restriction of growth perpendicular to the suture, thus placing higher than normal tension on the suture, resulting in bony islands within the membranous portion [2]. In another study on crania obtained from archeological sites [3], the crania with evidence of isolated sagittal craniosynostosis were found to have an increased number of posteriorly placed wormian bones. The author concluded that wormian bone development in posteriorly placed sutures may be affected more by environmental forces than in the anteriorly placed sutures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that this may occur due to restriction of growth perpendicular to the suture, thus placing higher than normal tension on the suture, resulting in bony islands within the membranous portion [2]. In another study on crania obtained from archeological sites [3], the crania with evidence of isolated sagittal craniosynostosis were found to have an increased number of posteriorly placed wormian bones. The author concluded that wormian bone development in posteriorly placed sutures may be affected more by environmental forces than in the anteriorly placed sutures.…”
Section: Discussionmentioning
confidence: 99%
“…The author concluded that wormian bone development in posteriorly placed sutures may be affected more by environmental forces than in the anteriorly placed sutures. This would suggest that the development of anterior fontanelle wormian bone could be genetically influenced [3]. If this indeed is the case, it would mean that children with an anterior fontanelle wormian bone could have a genetic basis for concomitant sagittal craniosynostosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that the variations in appearance shapes of the sutural bones and its incidence have been recognized in previous radiological and anatomical studies, it has been observed that the pattern of intrasutural bone was not as simple as had been reported many authors (6,7,11,10,18,19,21,22,(28)(29)(30). However, in adult skulls, the location of the preinterparietal bones is different; they are found at the lambda.…”
Section: Localizationmentioning
confidence: 95%
“…The testability and reliability of methods are necessary to establish that conclusions are objectively arrived at, rather than reached through mere subjective opinion. The Daubert standard for evaluations by a scientific expert is higher than for most physical anthropology publications, in which papers can be published despite questionably supported conclusions, methodological problems, and reliability concerns (Weaver, 1980;Henneberg, 1996, 2001;O'Loughlin, 2004;cf. Donnelly et al, 1998;Hill, 2000;Scheuer, 2002;Wilczak and Ousley, 2005).…”
Section: Evidencementioning
confidence: 98%